Diagnosing dying: an integrative literature review. Issue 3 (29th April 2014) - Kennedy, Catriona; Brooks-Young, Patricia; Brunton Gray, Carol; Larkin, Phil; Connolly, Michael; Wilde-Larsson, Bodil; Larsson, Maria; Smith, Tracy; Chater, Susie
Abstract : Background: To ensure patients and families receive appropriate end-of-life care pathways and guidelines aim to inform clinical decision making. Ensuring appropriate outcomes through the use of these decision aids is dependent on timely use. Diagnosing dying is a complex clinical decision, and most of the available practice checklists relate to cancer. There is a need to review evidence to establish diagnostic indicators that death is imminent on the basis of need rather than a cancer diagnosis. Aim: To examine the evidence as to how patients are judged by clinicians as being in the final hours or days of life. Design: Integrative literature review. Data sources: Five electronic databases (2001–2011): Cochrane Central Register of Controlled Trials (CENTRAL) on The Cochrane Library, MEDLINE, EMBASE, PsycINFO and CINAHL. The search yielded a total of 576 hits, 331 titles and abstracts were screened, 42 papers were retrieved and reviewed and 23 articles were included. Results: Analysis reveals an overarching theme of uncertainty in diagnosing dying and two subthemes: (1) 'characteristics of dying' involve dying trajectories that incorporate physical, social, spiritual and psychological decline towards death; (2) 'treatment orientation' where decision making related to diagnosing dying may remain focused towards biomedical interventions rather than systematic planning for end-of-life care. Conclusions: The findings of this review support the explicit recognition of 'uncertainty in diagnosing dying' and the need to work with and within this concept. Clinical decision making needs to allow for recovery where that potential exists, but equally there is the need to avoid futile interventions.